Human survival – core beliefs for sustainable development in globalization - PHAM, Khue Dinh; Quoc, Nguyen Anh (Edelweiss Applied Science and Technology, 2025)
The article analyzes the belief in humanity’s existence and sustainable development in the context of globalization; belief in human adaptability and creativity is the key to maintaining stability and development in the face of climate change, inequality, and conflict. Globalization brings opportunities for cooperation but also poses many challenges. The development of science and international cooperation helps people improve their quality of life while promoting movements to protect human rights and the environment. However, uncertainties such as fake news, environmental crises, and social inequality can erode people’s confidence. The article emphasizes the role of education in raising awareness of global citizenship and encouraging positive actions to solve international problems. At the same time, cooperation and sharing among individuals, organizations, and countries are the foundation for building a sustainable society. In addition, the study also assesses the impact of technology on human trust, pointing out that although technology creates many opportunities, it also poses risks, such as dependence on machines and digital inequality. Therefore, people need to balance innovation and human values. Since belief in sustainable existence and development requires community efforts, humanity must build a society that respects truth, creativity, and responsibility for a safe and prosperous future.